Colour tuning and enhancement of gel-based electrochemiluminescence devices utilising Ru(ii) and Ir(iii) complexes. Issue 76 (6th September 2019) - Soulsby, Lachlan C.; Doeven, Egan H.; Pham, Tien T.; Eyckens, Daniel J.; Henderson, Luke C.; Long, Benjamin M.; Guijt, Rosanne M.; Francis, Paul S.
Abstract : Combining luminophores in ratios that compensate for energy transfer provides a range of new emission colours for gel-based electrochemiluminescence devices. Abstract : Combining luminophores in ratios that compensate for energy transfer provides a readily selectable range of new emission colours for gel-based electrochemiluminescence devices (ECLDs). A novel blue ECLD luminophore is also introduced and shown to enhance the intensity of the conventional green emitter through a mixed annihilation ECL mechanism. Peak-to-peak voltages were minimised using asymmetric potential pulse sequences, which increased the longevity of the ECLD emission.